Dikotomi Kendali Menurut Stoikisme dalam Pembinaan Calon Imam - Angelus Narwastu Gerald; Reinaldy Noval Pasapan; Klaudius Regis Selang (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2025)
The Church authorities have established a number of criteria and indicators in the formation of candidates for the priesthood. In fulfilling these requirements, candidates are likely to have emotions of anxiety and worry. By using the literature review method of data collection, the author would like to show that the practice of Stoicism's Dichotomy of Control can be a way to prevent negative emotions in candidates for the priesthood. A proper understanding of the Dichotomy of Control and its application in the daily lives of priestly candidates can help them to direct their focus only on things that can be controlled. The study shows that the practice of the Dichotomy of Control according to Stoicism can help priestly candidates to avoid the psychological pressure that appears in the formation period. The results also show that the Dichotomy of Control can help direct the priest candidates' concern to things that can be controlled within themselves. Therefore, they can develop a mature personality freely, without psycholgical pressure and negative emotions. Abstrak Otoritas Gerejawi telah menetapkan sejumlah pedoman dan indikator dalam pembinaan calon imam. Dalam usaha memenuhi sejumlah syarat tersebut para calon imam rentan untuk mengalami perasaan khawatir dan cemas. Dengan menggunakan metode pengumpulan data studi pustaka penulis ingin memperlihatkan penerapan Dikotomi Kendali ala Stoikisme dapat menjadi jalan untuk mencegah emosi negatif dalam diri para calon imam. Pemahaman yang tepat mengenai Dikotomi Kendali dan penerapannya dalam kehidupan para calon imam dapat membantu para calon imam untuk mengarahkan fokus hanya pada hal-hal yang dapat dikendalikan. Dengan demikian para calon imam bisa membangun kepribadian yang matang secara merdeka, tanpa tekanan psikolgis dan emosi negatif.